(untitled) (Лучшие интеллектуальные исследования, 2024)
The role of nursing in surgical processes is of great importance. Nurses not only monitor the patient’s condition but also play a critical role in ensuring the surgical process is effective and safe. In surgery, nurses provide a crucial part of the medical care for patients, and the role of skilled nurses is significant in organizing and delivering this care. This article analyzes the role, duties, and significance of nursing in surgery.